EVALUATION OF 3 DIFFERENT AGNOR COUNTING METHODS IN ADVANCED-CARCINOMA OF THE PROSTATE - (:unkn) unknown (WILEY, 1995)
We applied the silver staining of nucleolar organizer regions (AgNOR) technique to the pretreatment biopsies of 50 cases of advanced prostate cancer. Three different counting methods were utilized in the enumeration of AgNORs. All methods yielded statistically significant differences of mean AgNOR counts of groups defined by high and low WHO, and by Gleason grades. However, there was overlap among groups, and further analysis of counts by grouping of patients according to their stage, response to treatment, and prognosis was not conclusive. Replicate counts were performed in 10 cases. While intraobserver reproducibility was high by all methods, only the second counting method yielded nonsignificant interobserver variability. There was a significant intratumoral heterogeneity of AgNOR scores. Lack of technical standardization, low reproducibility, and lack of correlation with prognosis limit the use of AgNOR counts in advanced carcinoma of the prostate. (C) 1995 Wiley-Liss, Inc.
Keywords: NUCLEOLAR ORGANIZER REGIONS; PROSTATE CANCER; PROGNOSIS; NUCLEOLAR ORGANIZER REGIONS; CANCER; PROGNOSIS; PROTEINS